Duration of fermentation affects microbiome composition and biological activity of an Indian traditional formulation – Panchagavya - Gemini Gajera; Snehal Funde; Hanmanthrao Palep; Vijay Kothari (Journal of Ayurveda and Integrative Medicine, 2024)
Objective: This study aimed at investigating whether the duration of fermenting Panchagavya (PG) preparation in copper vessel affects its biological activity and microbiome composition. Materials and methods: Prophylactic potential of PG against bacterial infection was assessed through an in vivo assay employing the nematode worm Caenorhabditis elegans as a model host. Bacterial diversity of the PG samples was revealed through metagenomic analysis. Results: Duration of fermentation was found to affect biological activity as well as microbiome composition of the PG samples. PG-samples fermented ≥60 min lost their prophylactic potential, and develop anthelmintic activity. Bacterial phyla whose relative abundance was significantly different between the prophylactic and anthelmintic PG samples were Planctomycetota, Proteabacteria, Bacteroidota, Verrucomicrobiota, Patescibacteria, Acidobacteriota, Chloroflexi, Firmicutes and Campilobacterota. Conclusion: This study validates the prophylactic potential of Panchagavya against bacterial pathogens, and shows that duration of the fermentation time while preparing PG can have profound effect on its biological activities. Biological activities of PG samples seem to have a correlation with their inherent microbial community. Metagenomic profiling can be an effective tool for standardization of PG formulations.